The Add-On Effect of Solifenacin for Patients with Remaining Overactive Bladder after Treatment with Tamsulosin for Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Obstruction - Naoya Masumori; Taiji Tsukamoto; Masahiro Yanase; Hiroki Horita; Masaharu Aoki (Advances in Urology)
Objectives. To investigate the add-on effect of solifenacin for Japanese men with remaining overactive bladder (OAB) symptoms after tamsulosin monotherapy for lower urinary tract symptoms (LUTS) suggestive of benign prostatic obstruction (BPO) in real-life clinical practice. Methods. Patients aged ≥ 50 having remaining OAB symptoms (≥ 3 of OAB symptom score (OABSS) with ≥2 of urgency score) after at least 4 weeks treatment by 0.2 mg of tamsulosin for BPO/LUTS received 2.5 or 5.0 mg of solifenacin for 12 weeks. The International Prostate Symptom Score (IPSS), QOL index and OABSS, maximum flow rate (Qmax) and postvoid residual urine volume (PVR) were determined. Results. A total of 48 patients (mean age 72.5 years) completed the study. There were significant improvement in IPSS (15.1 to 11.2) and QOL index (4.2 to 3.0) by add-on of solifenacin. Although the IPSS storage symptom score was significantly improved, there were no changes observed in the IPSS voiding symptom score. The OABSS showed significant improvement (8.0 to 4.8). No changes were observed in Qmax and PVR. Conclusions. Under the supervision of an experienced urologist, the additional administration of solifenacin to patients with BPO/LUTS treated with tamsulosin, is effective in controlling remaining OAB symptoms.